What's Wrong with Homophobic Bakeries? A Critical Discussion of Discrimination and its Interaction with Political Freedoms and Religious Conscience, Drawing on the Asher's Bakery Case in Northern Ireland and Kasper Lippert-Rasmussen's Theory of Discrimination - Lawrence, David (Ethical theory and moral practice, 2019)
The Asher's Bakery case raises questions around discrimination against political causes and freedom of religious conscience. Using the Asher's case, this essay builds on Kasper Lippert-Rasmussen's work to develop a theory of discrimination which accounts for discrimination of political causes. The essay explores the normative implications of this account including the rights members of salient political causes, and discusses various objections; in particular, how discrimination claims should be balanced against freedom of religious conscience in a liberal society and how religion's 'specialness' can be defended. By offering a critique of the Asher's case, the essay aims to provide a framework for dealing with similar cases where claims of discrimination from political groups meet claims of religious discrimination.